THE ECONOMIC IMPACT OF THE NATIONAL HEALTH INSURANCE (JKN) PROGRAM ON ACCESS AND QUALITY OF MIDWIFERY SERVICES - Yeni Trisna Purba; Arthauly Gracia Sinaga; Putri Handayani Simbolon (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
The National Health Insurance (JKN) program in Indonesia, through the Social Security Administering Agency (BPJS Kesehatan), is one of the largest universal health coverage schemes in the world. Its primary goal is to reduce financial barriers to access to healthcare. In the context of obstetric services, JKN is expected to improve pregnant women's access to antenatal care, safe delivery in health facilities, and postpartum care. This literature review examines the economic impact of JKN on the accessibility of obstetric services, changes in service utilization patterns, and its implications for the quality of care. The objective is to analyze how JKN has transformed the landscape of obstetric services in Indonesia and identify areas requiring further improvement to achieve equitable and quality universal health coverage.